Tempus fugit: time pressure in risky decisions - Kocher, Martin; Pahlke, Julius; Trautmann, Stefan T. (Münchener Wirtschaftswissenschaftliche Beiträge, 2011)
We study the effects of time pressure on risky decisions for pure gain prospects, pure loss prospects, and mixed prospects involving both gains and losses. In an experiment we find that risk aversion for gains is robust under time pressure whereas risk seeking for losses turns into risk aversion under time pressure. For mixed prospects, subjects become more loss averse and more gain seeking under time pressure, depending on the framing of the prospects. The results suggest the importance of aspiration levels under time pressure. We discuss the implications of our findings for decision making situations that involve time pressure.